2023
DOI: 10.1007/s00438-023-02036-y
|View full text |Cite
|
Sign up to set email alerts
|

Association of mitochondrial DNA variation with high myopia in a Han Chinese population

Abstract: High myopia (HM), which is characterized by oxidative stress, is one of the leading causes of visual impairment and blindness across the world. Family and population genetic studies have uncovered nuclear-genome variants in proteins functioned in the mitochondria. However, whether mitochondrial DNA mutations are involved in HM remains unexplored. Here, we performed the first large-scale whole-mitochondrial genome study in 9613 HM cases and 9606 control subjects of Han Chinese ancestry for identifying HM-associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Considering the fact that numerous transcription factors and coactivators, including SREBP, PGC-1α and others, are involved in regulation of the expression of enzymes catalyzing the rate-limiting steps of liver glycolytic metabolic processes [ 55 ], it is reasonable to speculate that SREBP-related mechanisms may also induce alterations in both OCR and ECAR indices among HSSF cells obtained from eyes with various ALs, as shown in Figure 1 . To support our current evidence, it is shown that high myopia may be induced by oxidative stress base upon family and population genetic studies identifying the nuclear-genome variants within proteins related to mitochondrial function rationally suggesting the critical roles of mitochondrial variants in the molecular etiology of high myopia [ 56 ].…”
Section: Discussionmentioning
confidence: 65%
“…Considering the fact that numerous transcription factors and coactivators, including SREBP, PGC-1α and others, are involved in regulation of the expression of enzymes catalyzing the rate-limiting steps of liver glycolytic metabolic processes [ 55 ], it is reasonable to speculate that SREBP-related mechanisms may also induce alterations in both OCR and ECAR indices among HSSF cells obtained from eyes with various ALs, as shown in Figure 1 . To support our current evidence, it is shown that high myopia may be induced by oxidative stress base upon family and population genetic studies identifying the nuclear-genome variants within proteins related to mitochondrial function rationally suggesting the critical roles of mitochondrial variants in the molecular etiology of high myopia [ 56 ].…”
Section: Discussionmentioning
confidence: 65%